In vitro comparative evaluation of efficiency of XP-endo shaper, XP-endo finisher, and XP-endo finisher-R files in terms of residual root filling material, preservation of root dentin, and time during retreatment procedures in oval canals – A cone-beam computed tomography analysis - Kapasi, Khyati (J Conserv Dent, 2020)
BACKGROUND: In an oval-shaped canal, no single instrumentation systems were effective in absolute removing obturation. AIM: The aim of the study was to evaluate the performance of ProTaper Universal Retreatment (PTUR) system, XP-endo Shaper (XPS), XP-endo Finisher (XPF), and XP-endo Finisher-R (XPF-R) in removing root-canal filling material and preservation of sound dentin during retreatment procedure. METHODOLOGY: Root-canal preparation was performed on 60 mandibular premolars with oval-shaped canals using the ProTaper Gold file system. Preobturation scans were performed to measure canal volume of the canal and recorded. Obturation was performed and the samples were randomly assigned into four groups according to the retreatment protocol used (n = 15): H-file, PTUR files, PTUR followed by XPF file, and XPS supplemented with XPF-R file. After retreatment, the specimens were re-scanned and volumetric analysis of remaining root filling material, volume of the canal space were measured using EZ-3Di Software Version 5.0.0.2. All the data were subjected to one-way ANOVA and post hoc Tukey's test with a significance of 5%. RESULTS: XPS + XPF-R showed promising results in the removal of obturating material and preservation of root dentin than any other group. The difference is statistically significant. CONCLUSION: XPS + XPF-R removed gutta-percha more significantly without sacrificing the sound dentin along with instrumentation.